2010
DOI: 10.1097/opx.0b013e3181da8628
|View full text |Cite
|
Sign up to set email alerts
|

Local Steepening in Peripheral Corneal Curvature After Corneal Refractive Therapy and LASIK

Abstract: Both, surgical and non-surgical interventions show a mid-peripheral local corneal steepening. However, the narrower optic zone and higher midperipheral steepening with CRT seems to provide the potential to create a more relative peripheralmyopic increase in corneal power than LASIK, which may have implications in slowing down myopia progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 34 publications
4
36
0
3
Order By: Relevance
“…Steepening in the corneal curvature after LASIK and refractive therapy with gas-permeable contact lenses has been reported. 28,29 However, corneal manipulation can be associated with a risk for keratectasia. Several cases of corneal ectasia have been reported after LASIK and photorefractive keratectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Steepening in the corneal curvature after LASIK and refractive therapy with gas-permeable contact lenses has been reported. 28,29 However, corneal manipulation can be associated with a risk for keratectasia. Several cases of corneal ectasia have been reported after LASIK and photorefractive keratectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the change in the corneal curvature at the margins of the optical zone created. 29 Hence, we consider it important to study the aberration values for the different pupil diameters. To the best of our knowledge, the current study is the first to evaluate the recovery of the different corneal HOAs for 3-, 4-, 5-, 6-, and 7-mm-diameter pupils, after treatment with CRT for 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in HOAs induced by LASIK and ortho-k have been explained by the change in corneal curvature at the margins of the optical zone created. 29 Queirós et al 29 reported that the transition zone between central treated and peripheral untreated cornea is smoother in LASIK compared with ortho-k. This difference provides a higher change in corneal asphericity in ortho-k compared with LASIK.…”
Section: Discussionmentioning
confidence: 98%